Removal of volatile organic compounds using amphiphilic cyclodextrin-coated polypropylene - Lumholdt, Ludmilla; Fourmentin, Sophie; Nielsen, Thorbjørn T.; Larsen, Kim L. (Beilstein Journal of Organic Chemistry, 2014)
Polypropylene nonwovens were functionalised using a self-assembled, amphiphilic cyclodextrin coating and the potential for water purification by removal of pollutants was studied. As benzene is one of the problematic compounds in the Water Framework Directive, six volatile organic compounds (benzene and five benzene-based substances) were chosen as model compounds. The compounds were tested as a mixture in order to provide a more realistic situation since the wastewater will be a complex mixture containing multiple pollutants. The volatile organic compounds are known to form stable inclusion complexes with cyclodextrins. Six different amphiphilic cyclodextrin derivatives were synthesised in order to elucidate whether or not the uptake abilities of the coating depend on the structure of the derivative. Headspace gas chromatography was used for quantification of the uptake exploiting the volatile nature of benzene and its derivatives. The capacity was shown to increase beyond the expected stoichiometries of guest–host complexes with ratios of up to 16:1.
Keywords: amphiphilic cyclodextrins; polypropylene; static headspace chromatography; volatile organic compounds; water purification